A new look at atonement in Leviticus: the meaning and purpose of kipper revisited - Greenberg, James (Bulletin for biblical research supplements, 2019)
Exodus 30:11-16, Leviticus 1-7 -- The relationship between evils and the sanctuary -- Leviticus 11-15 -- Leviticus 8-10 -- Leviticus 16.